Intra-arterial chemoradiation therapy with weekly low-dose cisplatin for squamous cell carcinoma of the maxillary sinus. Issue 6 (June 2015) - Kaneko, T.; Tada, Y.; Maruya, S.; Takeishi, E.; Miura, K.; Masubuchi, T.; Fushimi, C.; Hasegawa, H.; Kamata, S.
Abstract A new intra-arterial chemoradiation regimen that involves infusing low-dose cisplatin in combination with definitive irradiation was used in 36 patients diagnosed with squamous cell carcinoma of the maxillary sinus. The safety and therapeutic efficacy of this regimen were reviewed retrospectively. An intra-arterial catheter was inserted in a retrograde manner into the target artery via the superficial temporal artery or occipital artery. Intra-arterial infusion was performed using cisplatin at a dose of 20–50 mg/m2 per week for 6–8 weeks. At the same time, sodium thiosulphate was infused as a neutralizing agent. Irradiation was performed at 60 Gy in 30 fractions. All 36 patients completed treatment. Grade 3 adverse events occurred in only seven patients (19.4%) and no grade 4 events were noted. As a primary therapy, the complete response rate was 83.3%, the partial response rate was 16.7%, and the overall response rate was 100%. The 2-year local control rate was 63.0%, and the 2-year overall survival rate was 75.5%. The 2-year preservation rate of the hard palate was 97.1%, that of the eyeball was 97.2%, and that of visual function was 94.4%. This treatment regimen can contribute to improving the quality of life of patients without reducing the curability of the therapy.